ISLAMIC BANKING STRATEGY IN SUBTAINABLE DEVELOPMEN - Maulida, Riska (Tawazuna, 2024)
In the presentation, this research is intended to analyze the role and influence of banking in sustainable development in Indonesia. Sharia banking is a financial institution that applies Islamic principles in which the implementation of shari'ah banking prohibits riba and applies profit sharing (ratio), and there is also an agreement between the two parties, namely the company and the customer. The research used is qualitative discriminatory research, Which in this study uses in the form of data collection obtained through literature such as journals, scientific articles, and also online books